A Simple Enzyme-Immunoassay (EIA) Test for Factor VIII-Related Antigen (VIIIAGN) - Ness, Paul M; Perkins, Herbert A (Thrombosis and Haemostasis, 1979)
An enzyme immunoassay (EIA) system has been developed to measure factor VIII- related antigen (VIIIAGN). This assay gives similar results to the commonly used Laurell electroimmunodiffusion (EID) assay for VIIIAGN as shown by comparison of both techniques with samples from healthy controls, patients with hemophilia A, and patients with von Willebrand’s disease. The assay also has a greater precision than the EID technique as demonstrated by multiple assays of aliquots of a single sample. The use of this EIA test for VIIIAGN is simple and employs inexpensive reagents and equipment. The use of expensive antisera is minimized. EIA for VIIIAGN has the advantage of increased sensitivity compared to Laurell EIA.